Implementasi Teknologi Blockchain Dalam Uang Digital: Potensi Dan Dampaknya Terhadap Sistem Keuangan Global - Sindy Aulia Sari; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of information technology and digitalization has transformed many aspects of life, including the global financial sector. In recent decades, technological innovations such as blockchain have accelerated the transformation of how we conduct transactions and manage assets, shifting processes from manual systems to more efficient digital ones. Blockchain, which underpins cryptocurrencies like Bitcoin, enables peer-to-peer transactions without intermediaries, enhancing security, transparency, and efficiency. However, despite offering many advantages, the implementation of this technology faces regulatory challenges that vary across countries and cybersecurity risks. Through a literature review, this study aims to analyze the benefits and risks of implementing blockchain in digital currency and its impact on the global financial system. The findings indicate that blockchain has significant potential to improve financial inclusion and operational efficiency. However, challenges such as the volatility of digital currencies and impacts on the traditional financial sector need to be addressed. With the introduction of Central Bank Digital Currency (CBDC), there is an opportunity for more effective monetary policy management. Therefore, investment in robust infrastructure and enhanced cybersecurity is crucial to ensure the safe and efficient adoption of blockchain technology.